Legal Education for MMU Students: Harmonization of Digital Health Service Regulations between Indonesia and Malaysia - Aris Prio Agus Santoso; Rahmaditya Khadifa Abdul Rozzaq Wijaya; Thinesh A/L R Ganesan (International Journal Of Community Service, 2026)
The digital transformation in healthcare through telemedicine, electronic medical records, and application-based platforms has significantly improved access and efficiency, yet it also raises critical legal challenges related to patient data protection, professional liability, and legal certainty. Differences in regulatory approaches between Indonesia and Malaysia highlight the need for comparative legal analysis and regulatory harmonization to ensure a safe, ethical, and sustainable digital health ecosystem. This Community Service Program aims to enhance the legal literacy of students at Multimedia University (MMU), Malaysia, while strengthening comparative understanding of digital health law in Indonesia and Malaysia. The program employs an educational capacity-building approach through international seminars, regulatory harmonization workshops, and case-based academic discussions. It also produces academic outputs, including learning modules, teaching materials, scientific publications, video documentation, and intellectual property submissions. The results demonstrate both empirical success and philosophical significance. Empirically, students’ understanding of telemedicine, data protection, and professional responsibility improved significantly, as shown by pre- and post-test evaluations. Philosophically, the program reflects the lag of law, Radbruch’s triad of legal values, and Rawls’ theory of justice by promoting equal access to legal knowledge. It also embodies Roscoe Pound’s concept of law as social engineering and applies legal hermeneutics through contextual interpretation. The comparative approach underscores the urgency of legal harmonization, while the constructivist learning model strengthens critical legal awareness. Furthermore, through the Integrative-Tetradic Realism Theory, the program integrates normative, social, moral, and empirical dimensions, contributing to a dynamic and justice-oriented legal education paradigm in the digital era.